Pacing Induced Cardiomyopathy: What is The Solution? - Butarbutar, Maruli Wisnu Wardhana; Raharjo, Sunu Budhi (Jurnal Kardiologi Indonesia, 2022)
ABSTRACT Background Right ventricular pacing is associated with adverse outcome including increased risks of cardiovascular morbidity and mortality. RV pacing causes abnormal ventricular activation results in an inefficient contraction pattern with ventricular dyssynchrony and loss of myocardial work that may lead to LV dilation, systolic dysfunction, and clinical HF. Pacing induced cardiomyopathy (PICM) is caused by chronic and high burden RV pacing that may occur several months or years after pacemaker implantation. Objective To present a case of pacing induced cardiomyopathy (PICM) managed by CRT-P implantation. Case Illustration A male, 56 years old, was referred from dr. M. Djamil General Hospital with CHF Fc II-III, s/p PPM DDDR due to high degree AV block (2016) and history of failed CRT-P implantation (2018). He complained DOE (+), PND (+) and OP (+) since April 2017. Physical examination revealed pansystolic murmur grade 2/6 at apex, no rales and no oedema at both legs. ECG showed pacing rhythm and intrinsic rhythm was type 2 second degree AV block and RBBB with QRS duration 150 ms. Echocardiography showed global hypokinetic and dilated LV (LV EDD 71 mm, LV ESD 63 mm) with progressively reduced EF 38% à 33% (Simpson), functional moderate MR and mild TR. CAG showed non-significant coronary artery stenosis with 20% stenosis at distal LAD. Patient was diagnosed as pacing induced cardiomyopathy (PICM). At catheter laboratory, there was stenosis of left subclavian vein. His-Bundle pacing (HBP) was planned at first, however CRT-P with biventricular epicardial pacing was then performed in which LV lead was inserted through right axillary vein. During follow up at general ward, ECG showed biventricular pacing rhythm. There was no signs and symptoms of heart failure. Patient was hospitalized for 3 days and then discharged in a good condition. Summary We reported a case of pacing induced cardiomyopathy in male patient 56 years old. Pacing induced cardiomyopathy is a complication of high burden RV pacing. Options to treat PICM once it has developed, or to prevent it from developing in the first place, may include conduction system pacing (e.g.: HBP) or CRT-P implantation.